The Relationship of Inclusive Leadership With Organization-Based Self-Esteem: Mediating Role of Climate for Inclusion - Sunaina Kuknor; Bhuvanesh Kumar Sharma; Mohammed L. Ouakouak (SAGE Open)
The present study examines the relationship between inclusive leadership (IL) and organization-based self-esteem (OBSE). Further, we examine the mediating role of climate for inclusion in this relationship. The authors present how inclusive leader behavior impacts employee psychological well-being through inclusion practices. From the 47 IT companies generated from Prowess IQ software, 352 IT/ITES working professionals in India were selected using purposive sampling, surveyed online, and analyzed using Smart PLS-SEM and bootstrapping methods. The study finds a significant positive relationship between IL and OBSE, partially mediated by one of the dimensions of climate for inclusion that is inclusion in decision making (DM). Inclusive leader behavior leads to an increase in the psychological well-being of an employee. Further, through climate for inclusion, the impact increases, implying that a culture that fosters inclusion is essential along with inclusive leader behavior. The study is among the few studies empirically examining the interrelationships between IL, OBSE, and climate for inclusion in an Indian context. In a diverse country like India, the study contributes to the developing area of inclusive leader behavior, leading to psychological employee well-being. The findings facilitate leaders and managers in understanding employee pulse toward leader behavior and inclusion practices and taking preventive measures if the effort is not perceived correctly. Further, through inclusive work practices, employee relations can be enhanced at the organizational level, leading to higher OBSE.